Women community portal / Nur Faidzah Leman - Nur Faidzah, Leman (2006)
With the evolving of internet in Malaysia and the arising of information through internet many things can be done via it. Women in Malaysia are among the independent women in the world. With the knowledge they have they can interpret what they want. The women community portal is about the place where the Malaysian women can visit and register and also share their opinions together in the forum. The women can get new information from the portal. This portal 'to be' will be developed by using Macromedia Dreamweaver MX 2004 with the PHP as the language and MySQL as the database.